REBRANDING OF UNIVERSITY POLITEHNICA OF BUCHAREST - Radu Mihail Sofrone (Journal of Industrial Design and Engineering Graphics, 2018)
In this paper is presented a concept of redesign of the logo of Politehnica University of Bucharest. The redesign process begins with the presentation of the current stage of visual identity, and continues with the processes of research, sketching and design. The logo can directly influence the attitude of the viewers towards the brand, so it is an important way of communicating between the brand and the public. The results obtained offer the public a new perspective on the technical university.